THE WILL TO MEANING OF THE MAIN CHARACTER IN THE STARS SHINE DOWN NOVEL BY SIDNEY SHELDON - Dipoputriningtyas, Ragilsagitta (LANTERN (Journal on English Language, Culture and Literature), 2014)
The purpose of this thesis wants to analyze the will to meaning and the meaning of life of Lara Cameron in The Stars Shine Down novel by Sidney Sheldon. The analysis uses intrinsic and existential psychology method, that is Logoterapy. Basic concepts of Logoterapy that are used in this analysis are the will to meaning, freedom, responsibility, spirituality, and meaning of life. In Logotherapy by Victor Frankl, there are three sources of meaning of life. In intrinsic method, will be analyzed about theme, plot, character and setting that are supports the analysis of the meaning of life of Lara Cameron. The result of this study is that Lara’s life shows that every moment in life has a meaning of life, and showing how human finds the meaning of life. In every condition, people always look for their meaning of life to live their life. Logotherapy helps us to understand about the meaning of life deeper.